2013
DOI: 10.1007/s00246-013-0764-7
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Mitral Regurgitation Predicts Risk of Death or Cardiac Transplantation in Children With Idiopathic Dilated Cardiomyopathy

Abstract: Clinical outcomes among children with idiopathic dilated cardiomyopathy (IDC) are diverse, which makes the decision as to when a patient should be listed for a cardiac transplantation challenging. This study aimed to determine echocardiographic and clinical variables that can help clinicians identify those at highest risk for death or cardiac transplantation. The study was a single-center, retrospective chart review of children with IDC. Patients younger than 18 years with a diagnosis of IDC, as defined by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recognition of the presence and severity of mitral regurgitation, especially a moderate/severe degree of mitral regurgitation, can be of great value for risk stratification, treatment decisions and prognosis prediction (2,3,21). Our studies have revealed that the indexed LVESD, LAESD, and MAA min are positively correlated with increasing grades of mitral regurgitation grading, and in particular, the indexed LVESD is sufficiently sensitive to detect moderate/severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recognition of the presence and severity of mitral regurgitation, especially a moderate/severe degree of mitral regurgitation, can be of great value for risk stratification, treatment decisions and prognosis prediction (2,3,21). Our studies have revealed that the indexed LVESD, LAESD, and MAA min are positively correlated with increasing grades of mitral regurgitation grading, and in particular, the indexed LVESD is sufficiently sensitive to detect moderate/severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 64%
“…In DCM patients, chamber dilatation and alteration in the geometric relationship of the mitral valve apparatus may lead to mitral regurgitation, particularly MAA dilatation. According to previous studies (2,3,21), the presence of mitral regurgitation is associated with a poor outcome, and a moderate/severe degree of mitral regurgitation remains an independent predictor for sudden cardiac death, heart failure, and mortality in DCM patients. Surgical correction for severe mitral regurgitation can improve patients' symptoms and quality of life, reduce hospital mortality, and reveal reverse LV remodeling (14,22).…”
Section: Discussionmentioning
confidence: 95%
“…Our findings might warrant surgical intervention for secondary mitral regurgitation in the paediatric populations. It is not uncommon for dilated cardiomyopathy patients to develop secondary mitral regurgitation, which results in progressive worsening of left ventricular function and is associated with unfavourable prognosis in children 2,3 as well as adult patients. [17][18][19] Furthermore, mitral repair has been established as an effective therapy leading to reverse left ventricular re-modelling in adult dilated cardiomyopathy patients with secondary mitral regurgitation refractory to medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Secondary mitral regurgitation, also known as functional mitral regurgitation, is commonly encountered during echocardiography in children with dilated cardiomyopathy, and secondary mitral regurgitation severity is associated with poor prognosis in paediatric dilated cardiomyopathy patients. 2,3 Surgical intervention for severe secondary mitral regurgitation has been attempted to control heart failure. [4][5][6] Secondary mitral regurgitation is caused by altered mitral valve geometry; left ventricular dilatation leads to increased mitral valve leaflet tethering, which impairs valve closure.…”
Section: Ilated Cardiomyopathy the Most Commonmentioning
confidence: 99%